2021
DOI: 10.1024/0301-1526/a000919
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava-syndrome

Abstract: Summary: Inferior vena cava syndrome (IVCS) is caused by agenesis, compression, invasion, or thrombosis of the IVC, or may be associated with Budd-Chiari syndrome. Its incidence and prevalence are unknown. Benign IVCS is separated from malignant IVCS. Both cover a wide clinical spectrum reaching from asymptomatic to highly symptomatic cases correlated to the underlying cause, the acuity, the extent of the venous obstruction, and the recruitment and development of venous collateral circuits. Imaging is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…The dose described can be either 37.5 Gy in 15 fractions or 40 Gy in 20 fractions, depending on the patients' general condition. Side effects include nausea, vomiting, anorexia, diarrhoea, and myelosuppression (69,70).…”
Section: Inferior Vena Cava Obstruction (Ivcs)mentioning
confidence: 99%
“…The dose described can be either 37.5 Gy in 15 fractions or 40 Gy in 20 fractions, depending on the patients' general condition. Side effects include nausea, vomiting, anorexia, diarrhoea, and myelosuppression (69,70).…”
Section: Inferior Vena Cava Obstruction (Ivcs)mentioning
confidence: 99%
“…The former includes puncture site complications, improper positioning, delivery system complications, tilting, and incomplete deployment; the latter includes IVC-related thrombosis, filter fracture, vascular perforation, and vascular-enteric fistula [ 7 , 8 ]. Research has found that IVCT is the most common complication of filter implantation [ 9 ], and the presence of the filter increases the risk of lower extremity DVT, particularly when anticoagulation therapy is not administered [ 10 ]. A meta-analysis conducted by Angel et al [ 11 ] revealed an occurrence rate of 4.1% for IVC thrombosis or occlusion after IVCF insertion, with symptomatic cases accounting for 0.8% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing IVC stenting in particular remain limited and are commonly reported in the context of heterogeneous patient cohorts including SVC obstructions as well [ 9 , 15 – 17 ]. One major reason for this fact is that malignant IVC obstruction is a rare condition [ 18 ].…”
Section: Discussionmentioning
confidence: 99%